Pengaruh Kepemimpinan Transformasional Dan Budaya Organisasi Terhadap Kinerja Karyawan Pt. Avia Citra Dirgantara Malang - Muhammad Hasin; Abd Kodir Djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This study was conducted with the aim of knowing the description of transformational leadership and organizational culture on employee performance, to find out whether transformational leadership and organizational culture requires simultaneous support for employee performance, to find out whether transformational leadership is related to employees, to find out employee performance. This study uses employees of PT. Avia Citra Dirgantara who participated 153 people who participated in the research which was conducted in August 2019 to December 2019. Analysis of the data used in this study were: Validity test, reliability test, reliability test, multicollinearity test, heteroscedasticity test, heteroscedasticity test, multiple linear regression analysis, and hypothesis testing. With the results of the study: 1.) Leadership positive and significant transformation on employee performance. 2.) Organizational culture has a positive and significant effect on employee performance. 3.) Transformational leadership and organizational culture together (simultaneously) have a positive and significant effect on employee performanceKeyword :Transformational Leadership, Organizational Culture, Employee Performance